The Influence of the SQ4R Learning Model on Learning Outcomes Student - Astiza, Diaz Arida; Hidayatulloh, Muhammad Kris Yuan; Ashoumi, Hilyah (APPLICATION: Applied science in Learning Research, 2023)
This research aims to test whether or not there is an influence of the SQ4R learning model (Survey, Question, Read, Reflect, Recite, Review) on the learning outcomes of class VIII B students at MTsN 8 Jombang. This research uses a quantitative approach using quasi-experimental methods. The sample used was 38 class VIII students at MTsN 8 Jombang and was taken using a purposive sampling technique. Data collection techniques use observation sheets and tests to obtain data related to student learning outcomes. The results of this research show that the SQ4R learning model (Survey, Question, Read, Reflect, Recite, Review) has a significant influence on student learning outcomes in the basic competency of analyzing halal food and drink provisions, proven through t-test analysis with t results - count > t- table (270.683 > 2.042) and sig value. (2-tailed) of 0.000 or <0.05.